Sternenmomente. Karlheinz Stockhausen und die Morphologie der Zeit (De Musica, 2020)
The article tries to investigate the problem of time by following a dialectical and morphological approach derived from Goethe’s studies on nature and translated into a philosophy of time and history by Benjamin, but also from Husserl’s internal time consciousness. This research focuses especially on composers like Messiaen, Stockhausen, Xenakis and others. If Beethoven’s conception of time was teleological and monistic – just as the Hegelian one – Messiaen elaborated a dualistic and Stockhausen a pluralistic one. More in detail the research involves concepts like translation, aion and chronos, thus eternity and continuity in time or the discretional instant and the continuity of duration. Starting with the musical point of view it becomes also possible to take a look at the way, the several dimensions of time and their combinations work in other human spheres like history and policy or life and death.